2016
DOI: 10.1016/j.mambio.2016.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Activity patterns of ocelots and their potential prey in the Brazilian Pantanal

Abstract: Camera trapping has been widely used to study different aspects of animal ecology, increasing scientific knowledge and helping in conservation initiatives. Recently, some studies demonstrated the use of this technique to study temporal predator-prey interactions, most of which focused on large felids. In this study, we investigate the activity patterns of the ocelot (Leopardus pardalis)-a medium-sized neotropical cat -and its known potential prey in the Brazilian Pantanal using photographs taken by camera trap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 34 publications
2
22
1
4
Order By: Relevance
“…This nocturnal behaviour of ocelot may reflect the activity of their favourite small prey (Bianchi et al, 2014), which also tends to be nocturnal (Emmons, 1987). In fact, Porfirio et al (2016a) demonstrated that ocelots tend to tailor their activity to that of their potential prey, probably in an attempt to increase encounters. Jaguars in Amolar Mountain Ridge exhibited cathemeral behaviour, a pattern different of the observed in other areas of the Pantanal (Crawshaw & Quigley, 1991;Foster et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…This nocturnal behaviour of ocelot may reflect the activity of their favourite small prey (Bianchi et al, 2014), which also tends to be nocturnal (Emmons, 1987). In fact, Porfirio et al (2016a) demonstrated that ocelots tend to tailor their activity to that of their potential prey, probably in an attempt to increase encounters. Jaguars in Amolar Mountain Ridge exhibited cathemeral behaviour, a pattern different of the observed in other areas of the Pantanal (Crawshaw & Quigley, 1991;Foster et al, 2013).…”
Section: Resultsmentioning
confidence: 98%
“…The remaining records were eliminated from the analysis to reduce bias (Ross et al, 2013). Then, the time of each picture was converted to solar time (Foster et al, 2013;Porfirio et al, 2016a), and observations were classified as diurnal (activity predominantly between 1 h after sunrise and 1 h before sunset), nocturnal (activity predominantly between 1 h after sunset and 1 h before sunrise) or crepuscular (period that last 1 h before to 1 h after sunrise and sunset) following Romero-Muñoz et al (2010). Based on the percentage of pictures in each category, species were classified as diurnal (< 15% of the observations were at night), nocturnal (> 85% of the observations were at night), mostly diurnal (15-35% of the observations were at night), mostly nocturnal (65-85% of the observations were at night), crepuscular (50% of the observations occurred during the crepuscular period), and the rest were classified as cathemeral (i.e.…”
Section: Nature Conservation Research заповедная наука 2018 3(2): 5mentioning
confidence: 99%
“…Like in many other similar studies we used the approach developed by Ridout & Linkie (2009) to estimate the activity patterns of each species using kernel density analysis (Foster et al, 2013;Ross et al, 2013;Bu et al, 2016;Ikeda et al, 2016;Porfirio et al, 2016;Marcon et al, 2017). This is a non-parametric method for evaluating the probability density function of a random variable (Worton, 1989), time of capture in our case.…”
Section: Discussionmentioning
confidence: 99%
“…This test indicates if there is a significant statistic difference between circular distributions, and it has been used to analysed data from 24 hours activity patterns (Romero-Muñoz et al, 2010;Hernández-SaintMartín et al, 2013;Porfirio et al, 2016). We used R package «circular» for this (Lund et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation